Penerapan Sanksi Pidana Dalam Perkara Tindak Pidana Penyalahgunaan Narkotika (Studi Kasus: Putusan Mahkamah Agung RI Nomor 3790 K/PID.SUS/2020) (DiH: Jurnal Ilmu Hukum, 2022)
Law enforcement against narcotics abusers is also considered troubling because it does not create legal certainty. Namely the application of material criminal law by judges in the decision of the Supreme Court of the Republic of Indonesia Number 3790 K/PID.SUS/2020 in the Cassation decision on January 13, 2021 against the Defendant/Inmate Prasetyo Febriono. Then in legal considerations, the judge in passing a decision on case Number 3790 K/PID.SUS/2020 in the Cassation decision dated January 13, 2021 against the defendant Prasetyo Febriono was not appropriate based on normative and sociological juridical considerations and by looking at valid evidence. Because Defendant III (Prasetyo Febriono) is a criminal act of Narcotics Abuse Category I for himself in accordance with Article 127 Paragraph (1) letter a of Law No. 35 of 2009 on Narcotics and it is really the defendant who is guilty of doing it. The Panel of Judges based on the facts at the trial considered that the defendant could be held accountable for his actions with the consideration that at the time of committing his actions the defendant was aware of the consequences it caused and did not discourage his intentions, the perpetrator in carrying out his actions was in good physical condition and capable of considering elements against the law and there is no reason for the abolition of the crime. The research method used is normative legal research with a research approach that includes a statutory approach and a conceptual approach. From research conducted by researchers get the following results: 1). The application of material criminal law by the judge in the Supreme Court of the Republic of Indonesia Number 3790 K/PID.SUS/2020 in the Cassation Decision dated January 13, 2021 against the defendant/convict Prasetyo Febriono is not appropriate because Defendant III is a criminal act of narcotics abuse Category I for himself which is in accordance with Article 127 Paragraph (1) letter a of Law No. 35/2009 and it is really the defendant who is guilty of doing so. 2). As for legal considerations, the judge in ruling on case Number 3790 K/PID.SUS/2020 in the Cassation decision dated January 13, 2021 against the defendant Prasetyo Febriono was not appropriate based on normative and sociological juridical considerations and by looking at valid evidence. Keywords: legal considerations; material criminal; narcotics abuse Abstrak Penegakan hukum terhadap pelaku penyalahgunaan narkotika juga dinilai meresahkan karena tidak mewujudkan kepastian hukum. Yaitu penerapan hukum pidana materiil oleh hakim pada putusan Mahkamah Agung Republik Indonesia Nomor 3790 K/PID.SUS/2020 dalam putusan Kasasi tanggal 13 Januari 2021 terhadap Terdakwa/Narapidana Prasetyo Febriono. Kemudian dalam pertimbangan hukum, hakim dalam menjatuhkan putusan pada perkara Nomor 3790 K/PID.SUS/2020 dalam putusan Kasasi tanggal 13 Januari 2021 terhadap terdakwa Prasetyo Febriono tidak sesuai berdasarkan pertimbangan yuridis normatif dan sosiologis dan dengan melihat alat-alat bukti yang sah. Karena terdakwa III (Prasetyo Febriono), merupakan tindak pidana Penyalahgunaan Narkotika golongan I bagi diri sendiri yang sesuai dengan Pasal 127 Ayat (1) huruf a UU R.I No 35 tahun 2009 Tentang Narkotika dan itu benar-benar terdakwalah yang bersalah melakukannya. Majelis Hakim berdasarkan fakta-fakta di persidangan menilai bahwa terdakwa dapat mempertanggung jawabkan perbuatannya dengan pertimbangan bahwa pada saat melakukan perbuatannya terdakwa sadar akan akibat yang di timbulkannya dan tidak mengurungkan niatnya, pelaku dalam melakukan perbuatannya dalam keadaan sehat jasmani dan cakap untuk mempertimbangkan unsur melawan hukum serta tidak adanya alasan penghapusan pidana. Metode penelitian yang digunakan yaitu penelitian hukum normatif dengan pendekatan penelitian meliputi pendekatan perundang–undangan (statute approach) dan pendekatan konseptual (conceptual approaach). Hasil penelitian ini menunjukkan bahwa: 1). Penerapan hukum pidana materil oleh hakim pada Putusan Mahkamah Agung Republik Indonesia Nomor 3790 K/PID.SUS/2020 dalam Putusan Kasasi tanggal 13 Januari 2021 terhadap terdakwa/narapidana Prasetyo Febriono tidak tepat karena terdakwa III, merupakan tindak pidana penyalahgunaan narkotika Golongan I bagi diri sendiri yang sesuai dengan Pasal 127 Ayat (1) huruf a UU No.35/2009 dan itu benar-benar terdakwalah yang bersalah melakukannya. 2). Adapun pertimbangan hukum, hakim dalam menjatuhkan putusan pada perkara Nomor 3790 K/PID.SUS/2020 dalam putusan Kasasi tanggal 13 Januari 2021 terhadap terdakwa Prasetyo Febriono tidak sesuai berdasarkan pertimbangan yuridis normatif dan sosiologis dan dengan melihat alat-alat bukti yang sah. Kata kunci: penyalahgunaan narkotika; pertimbangan hukum; pidana materiil